A Method of Network Access Control for Ensuring Network Infrastructure Security Based on Severing Superfluous Network Connectivity - Shilova, A. D.; Vorob’eva, A. A. (Automatic control and computer sciences, 2023)
— This paper discusses problems of improving network infrastructure security. A network infrastructure is developed; an access control method based on severing superfluous network connectivity between subjects and objects is proposed and assessed; and potential directions of its development are outlined. This method can be used for network segmentation.